2022
DOI: 10.3390/nu14153224
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Offers No Additional Benefit to Lifestyle Intervention on Cardiometabolic Status in Patients with Non-Alcoholic Fatty Liver Disease

Abstract: Cardiovascular disease (CVD) is the leading cause of death in patients with non-alcoholic fatty liver disease (NAFLD). Curcumin has been shown to exert glucose-lowering and anti-atherosclerotic effects in type 2 diabetes. Hence, we investigated curcumin’s effects on atherogenesis markers, fatty liver, insulin resistance, and adipose tissue-related indicators in patients with NAFLD. In this secondary analysis of a 12-week randomized controlled trial, fifty-two patients with NAFLD received lifestyle modification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 80 publications
1
8
0
Order By: Relevance
“…From now on, the clinical trials of curcumin are primary about cancer [ 214 ], AD [ 215 ], metabolic syndrome [ 216 ], polycystic ovarian syndrome [ 217 ] et al In addition, clinical trials of nanocurcumin [ 190 ] and its bioavailability research [ 218 ] were also reported. Many clinical trials have shown the role of curcumin in improving diseases, but small number of clinical trials also found that curcumin has no significant benefit to related diseases [ 219 ]. The related information about curcumin clinical trials was shown in Table 4 .…”
Section: Curcumin Clinical Application Statusmentioning
confidence: 99%
“…From now on, the clinical trials of curcumin are primary about cancer [ 214 ], AD [ 215 ], metabolic syndrome [ 216 ], polycystic ovarian syndrome [ 217 ] et al In addition, clinical trials of nanocurcumin [ 190 ] and its bioavailability research [ 218 ] were also reported. Many clinical trials have shown the role of curcumin in improving diseases, but small number of clinical trials also found that curcumin has no significant benefit to related diseases [ 219 ]. The related information about curcumin clinical trials was shown in Table 4 .…”
Section: Curcumin Clinical Application Statusmentioning
confidence: 99%
“…Subsequent findings from a randomized controlled trial involving 52 NAFLD patients corroborated these conclu- markers, were observed. Nonetheless, the likelihood of severe fatty liver and metabolic syndrome was reduced (Naseri et al, 2022).…”
Section: A Clinical Glimpse At Polyphenolic Compounds Protecting Agai...mentioning
confidence: 99%
“…However, no further effects of curcumin on cardiometabolism, including adipose tissue‐related indicators, atherogenic markers, and insulin resistance markers, were observed. Nonetheless, the likelihood of severe fatty liver and metabolic syndrome was reduced (Naseri et al, 2022).…”
Section: A Clinical Glimpse At Polyphenolic Compounds Protecting Agai...mentioning
confidence: 99%
“…One clinical study showed that synbiotic (Lactobacillus sporogenes, inulin, and β-carotene) had favorable effects on insulin, HOMA-IR, HOMA-B, triglycerides, VLDL-cholesterol, total-/HDL-cholesterol ratio, NO, and GSH levels (Asemi et al, 2016). Many studies have proved the well therapeutic effect of synbiotics without any adverse reactions (Chiou et al, 2021;Naseri et al, 2022;Zhao et al, 2022).…”
Section: Introductionmentioning
confidence: 99%